Bilateral Cryptococcal Choroiditis in a Human Immunodeficiency Virus-Infected Patient: A Case Report - Sara Sanfilippo; Bastien Docquier; Paul Louis Schrooyen; Dorine Makhoul; Aurélie Le (Case Reports in Ophthalmology, 2024)
Introduction: In this case report, we present a rare case of bilateral cryptococcal choroiditis following a diagnosis of meningitis in a 38-year-old woman with HIV. Case Presentation: A Colombian woman, newly diagnosed with HIV, presented with respiratory distress followed by meningeal syndrome. Further evaluation revealed cryptococcal meningitis caused by Cryptococcus neoformans, confirmed through cerebrospinal fluid analysis and brain magnetic resonance imaging. The patient reported mild blurred vision, prompting an ophthalmic examination that included indocyanine green angiography. The findings revealed signs of HIV retinopathy and multifocal choroidal lesions in both eyes, suggestive of choroidal cryptococcosis. Treatment involved intravenous administration of amphotericin B and flucytosine, followed by oral fluconazole. Subsequently, the choroidal lesions gradually regressed, and regular monitoring demonstrated no signs of recurrence. Conclusion: Cryptococcal choroiditis, though exceptionally rare, can occur in HIV-positive patients with disseminated cryptococcosis. Ophthalmologists should maintain a high index of suspicion for opportunistic infections, even in the absence of pronounced ocular symptoms, particularly in immunocompromised individuals. Early diagnosis and appropriate treatment are crucial for achieving favorable outcomes in such cases.